DIGITALIZATION OF LOGISTICS ENTERPRISES' ACTIVITIES (Web of Technology: Multidimensional Research Journal, 2025)
This article examines the challenges and opportunities for developing digital logistics in Uzbekistan. The primary objective of the study is to identify ways to enhance efficiency and achieve economic benefits through the digitalization of logistics processes. The study explores the impact of digital technologies, including the advantages of IoT and electronic management systems. Based on statistical analysis, international practices, and local case studies, scientific-methodological and practical recommendations are proposed.